(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
In this paper we examine if Slovak retail gasoline and diesel prices respond more quickly when crude oil price rises rather than when it decreases. The error correction model with irreversible behaviour of explanatory variables is considered to be basic tool for the analysis of asymmetric retail price reaction of gasoline and diesel. The explanatory variable is divided into two variables, the positive and the negative differences implying a price increase and a price decrease. Due to the link between the gasoline and diesel markets, we assume a common co-integration relationship. Therefore, we also estimate vector error correction model in our analysis. The both model approaches reject expected asymmetry in the retail price reactions on crude oil changes. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.